Behavioral inflexibility through overtraining is mediated by reduced mGluR1/5 signaling capacity in the dorsolateral striatum. - Vincent Paget-Blanc; Anna Cavaccini; Alessandra Longaretti; Luca Nava; Massimo Trusel; Anna Rocchi; Maria Pennuto; Elena Marcello; Fabrizio Gardoni; Barbara Greco; Raffaella Tonini (PLoS Biology, 2025)
The control of instrumental actions engages distinct behavioral strategies whose contributions are regulated with experience. Instrumental performance, which depends on the causal relationship between actions and their outcomes (A-O), relies on flexible, goal-directed control of behavior. Actions can become less sensitive to changes in action-outcome (A-O) contingencies with repetition, resulting in more inflexible, habitual behaviors. The loss of flexibility with repetition requires plasticity at corticostriatal circuits. However, the underlying molecular mechanisms are not yet established, and how these mechanisms specifically relate to the inability to adapt to new contingencies is unknown. In mice, we find that inflexible behavioral performance following overtraining of an appetitive instrumental task is associated with a reduced capacity of mGluR5 receptors in the dorsolateral striatum (DLS) to engage intracellular signaling in response to changes in action-outcome contingency. We also observed dichotomous modulation of timing-dependent synaptic depression (tLTD) at striatal projection neurons of the indirect (iSPNs) and direct (dSPNs) pathways. Preventing overstimulation of mGluR5 signaling through a homotypic process preserved behavioral sensitivity to changes in A-O contingencies despite overtraining, and averted the related biochemical and synaptic changes. Furthermore, mGluR5 couples to different signaling pathways to regulate tLTD in iSPNs and dSPNs. Our findings demonstrate that decreased signaling capacity of mGluR1/5, accompanied by cell-type-specific modulation of corticostriatal synapses in the DLS, represents a key molecular mechanism underlying overtraining-induced behavioral inflexibility.